2014
DOI: 10.1016/j.dnarep.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Pif1 family helicase Pfh1 facilitates telomere replication and has an RPA-dependent role during telomere lengthening

Abstract: Pif1 family helicases are evolutionary conserved 5′ to 3′ DNA helicases. Pfh1, the sole S. pombe Pif1 family DNA helicase, is essential for maintenance of both nuclear and mitochondrial DNAs. Here we show that its nuclear functions include roles in telomere replication and telomerase action. Pfh1 promoted semi-conservative replication through telomeric DNA, as replication forks moved more slowly through telomeres when Pfh1 levels were reduced. Unlike other organisms, S. pombe cells overexpressing Pfh1 displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…Noteworthy, a milder overexpression of Pfh1 Pif1 with pREP41 did not restore telomere length of D223Y cells (Supplementary Fig S6). Consistent with a recent study, we observed that overexpression of Pfh1 Pif1 by itself slightly lengthened the telomeres of a WT strain (Fig A, lanes 6, 7) (McDonald et al , ). Thus, among the tested helicases, only Pfh1 Pif1 was able to rescue the telomere defect of the D223Y mutant.…”
Section: Resultssupporting
confidence: 92%
“…Noteworthy, a milder overexpression of Pfh1 Pif1 with pREP41 did not restore telomere length of D223Y cells (Supplementary Fig S6). Consistent with a recent study, we observed that overexpression of Pfh1 Pif1 by itself slightly lengthened the telomeres of a WT strain (Fig A, lanes 6, 7) (McDonald et al , ). Thus, among the tested helicases, only Pfh1 Pif1 was able to rescue the telomere defect of the D223Y mutant.…”
Section: Resultssupporting
confidence: 92%
“…However, pfh1Δ spore clones, which divide only a few times before they arrest in G2 phase, have modestly shorter telomeres than wild type cells [53]. Moreover, over-expressing Pfh1 increases telomere length by a recombination-independent mechanism, and this lengthening does not occur in rad11-D223Y cells [54], in which telomerase action is inefficient [55]. As Pfh1 promotes telomere lengthening in a telomerase-dependent manner, it is unlikely to be an inhibitor of telomerase.…”
Section: Pif1 Family Helicases Affect Telomerasementioning
confidence: 99%
“…By both 2D gels and ChIP experiments, depleting cells of Pfh1 slows fork progression within telomeres [11,54]. …”
Section: Rrm3 and Pfh1 Helicases Promote Semi-conservative Replicamentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to ScPif1, S. pombe Pfh1 (PIF1-homolog-1) maintains mtDNA integrity. In addition, both ScPIF1 and SpPfh1 maintain telomeric DNA integrity and normal telomere length (SCHULZ AND ZAKIAN 1994;MCDONALD et al 2014). However, loss of Pfh1 is lethal (ZHOU et al 2002;PINTER et al 2008), while deletion of S. cerevisiae Pif1 is not, for reasons that are still not understood.…”
Section: Introductionmentioning
confidence: 99%